Mangrove distribution in Kilim River, Langkawi - Saad, Shahbudin; Ahmad, Zuhairi (2009)
Besides having commercial values, mangroves play major roles as coastal protection, buffer zone, and nursery grounds for various types of marine organisms. In Langkawi island, mangrove area stretched and occupied along the northeast coast of the island throughout the Kilim River, covered almost 48.0% or 1976.24 ha of its total mangrove area. It consists of 15 species which are dominated by Rhizophora spp. Factors of large area and technology and satellite imagery analysis in monitoring true Kilim's mangroves. From unsupervised ad supervised classification, mangroves in Kilim River can be discriminated into 1 group with acceptable 16.0% accuracy. Significant reflectance of each genus show almost similar patterns. Temporal studies on mangrove classification using high spectral data should be conducted in order to monitor the changes of mangrove reflectance. This change may affect the final results as temporal studies may consolidate classification accuracy.